2016
DOI: 10.1101/078741
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Co-expression networks reveal the tissue-specific regulation of transcription and splicing

Abstract: Gene co-expression networks capture biologically important patterns in gene expression data, enabling functional analyses of genes, discovery of biomarkers, and interpretation of regulatory genetic variants. Most network analyses to date have been limited to assessing correlation between total gene expression levels in a single or small sets of tissues. Here, we have reconstructed networks that capture a much more complete set of regulatory relationships, specifically including regulation of relative isoform a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 96 publications
(97 reference statements)
0
20
0
Order By: Relevance
“…A). This distinction is however empirical, and whole‐transcriptome sequencing data from a growing number of diverse tissue types suggests that the range of alternatively spliced human transcripts may be greater than previously appreciated. For most categories of splicing events, multiple splice site will be simultaneous present on the nascent pre‐mRNA.…”
Section: Overview Of the Splicing Process And The Spliceosomal Machinerymentioning
confidence: 99%
See 1 more Smart Citation
“…A). This distinction is however empirical, and whole‐transcriptome sequencing data from a growing number of diverse tissue types suggests that the range of alternatively spliced human transcripts may be greater than previously appreciated. For most categories of splicing events, multiple splice site will be simultaneous present on the nascent pre‐mRNA.…”
Section: Overview Of the Splicing Process And The Spliceosomal Machinerymentioning
confidence: 99%
“…The mRNA isoform composition varies profoundly across human tissues . It is therefore not surprising that some splicing regulators display tissue‐dependent expression patterns , resulting in corresponding cell type‐specific regulation of their target pre‐mRNA substrates.…”
Section: Splicing Regulation By Cis‐acting Sequence Features and Tranmentioning
confidence: 99%
“…Further, they showed that splicing QTLs are also enriched for genetic variants associated with several complex traits in Genome-Wide Association Studies (GWAS), demonstrating the potential importance of splicing misregulation in complex traits [22]. Previous work from our lab and others have shown that gene-by-environment interactions can impact both gene expression and complex traits [23,24,25,26,27,28]. While splicing QTLs have been identified both in humans and mice [22,29,30,31], less is known about how gene-by-environment interactions may affect RNA processing.…”
Section: Introductionmentioning
confidence: 99%
“…These hubs usually have important biological functions and generally play vital roles in the network. Based on the size of the network and analogous work in human studies (Saha et al, ), we define three types of hubs by their degrees, small hubs with degrees between 30 and 50, medium hubs with degrees between 50 and 80, and large hubs of degrees more than 80. A summary of nodes, edges, average degree per node, and the number of the hubs is shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Gao et al developed BicMix, a Bayesian biclustering method, to construct differential gene co‐expression networks (Gao, McDowell, Zhao, Brown, & Engelhardt, ). Saha et al () used this method to construct co‐expression networks on GTEx data across human tissues to study tissue‐specific regulation of transcription and splicing. Xiao, Moreno‐Moral, Rotival, Bottolo, and Petretto () developed a higher‐order generalized singular value decomposition method on multi‐tissue analysis of co‐expression networks.…”
Section: Introductionmentioning
confidence: 99%